(untitled) (Prithvi Academic Journal, 2018)
The 1960s era was one of the most divisive, turbulent periods in American history. In many ways, the decade was defined by the Counterculture Movement and by those who resisted the demands of a conformist society rooted in Cold War values. This historical study first contextualizes the emergence of the Counterculture Movement of the 1960s within the historical period of mid-century America. Next, the paper provides an analysis of the values of the Counterculture Movement expressed through music. Exploration of counterculture songs reveals that participants advocated the rejection of society through the expression of personal freedom, immediate gratification, anti-materialism, community, and free love. Furthermore, inquiry demonstrates that music was used as a vehicle to explain and promote the movement’s ideals. Ultimately, the study demonstrates the ways in which music of the Counterculture Movement reflected Americans’ broader questions of, and challenges to, the Cold War culture in the late- 1960s.